Data Without Dignity? A Critical Perspective on How Educational Assessment Systems Overlook the Financial and Safety Realities of Women Learners - Moses Mhide Kpum; Velisiwe Gasa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Educational assessment systems worldwide claim objectivity and meritocracy, yet they systematically fail to account for the gendered realities that shape women learners' access, performance, and persistence. This perspective paper critically examines how contemporary assessment frameworks, despite increasing datafication and loud claims of evidence-based practice, overlook the financial precarity and safety vulnerabilities that disproportionately affect women and girls in educational settings. The analysis draws on a critical synthesis of peer-reviewed empirical studies across diverse contexts, including South Asia, Sub-Saharan Africa, Europe, and North America, alongside policy documents from international organizations and recent large-scale quantitative and qualitative research. Assessment systems from primary through higher education are examined here. The paper is delimited to formal educational assessment contexts, standardized examinations, continuous assessment, and digital assessments, and focuses specifically on five categories of gendered barriers: period poverty, financial precarity, transportation and campus safety risks, intimate partner violence, and caregiving responsibilities. The analysis does not extend to informal assessment, workforce credentialing, or barriers arising from disability, though intersections with these are acknowledged where evidence permits. Through the lens of feminist epistemology, capability approach theory, and recent empirical evidence, the central argument holds that assessment systems function as technologies of inequality when they measure learning outcomes without acknowledging the material conditions required for dignified participation. Period poverty, transportation safety concerns, caregiving responsibilities, and economic vulnerability each create assessment disadvantages that are rendered invisible by ostensibly neutral measurement systems. In response, the paper proposes a dignity-centered assessment framework, one that treats safety and financial security as prerequisites for valid educational measurement rather than mere contextual variables. Concrete principles for gender-responsive assessment design are offered as a path toward transforming evaluation systems from instruments of exclusion into tools for genuine equity and empowerment.